Post a New Question


posted by .

I think am not getting it right bt cos its a little bit complicated t = square root of {V/ 1/f +1/g } make f subject of the formula

  • math -

    square both sides

    t^2 = v/(1/f + 1/g)
    t^2 = v/( (f+g)/(fg) )
    t^2 = vfg/(f+g)
    ft^2 + gt^2 = vfg
    ft^2 - vfg = -gt^2
    f(t^2 - vg) = -gt^2
    f = -gt^2/(t^2 - vg) or gt^2/(vg - t^2)

Answer This Question

First Name
School Subject
Your Answer

Related Questions

More Related Questions

Post a New Question